2021
DOI: 10.3390/antibiotics10060703
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Prescription by Spanish General Practitioners in Primary Dental Care

Abstract: The aim of this study was to analyze the antibiotics prescription habits, both prophylactically and therapeutically, of Spanish general dental practitioners in the management of endodontic infections in primary care. Two hundred Spanish general dental practitioners were asked to respond to a survey on indications for antibiotics prescription in the treatment of endodontic infections, being 190 general dentists (95%) included in the study. Data were analyzed using descriptive statistics and the chi-square test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…This study reflects the current state of knowledge and patient perception of antibiotic resistance and the use and need for systemic antibiotics in the treatment of pulpo-periapical infections. Previous studies [2,10,[14][15][16][17] have evaluated dentists' knowledge of antibioticprescribing habits. However, although it is known that dentists' prescribing habits are sometimes influenced by patient pressure, until now, no study had analyzed patients' knowledge and beliefs about antibiotic treatment in endodontics.…”
Section: Discussionmentioning
confidence: 99%
“…This study reflects the current state of knowledge and patient perception of antibiotic resistance and the use and need for systemic antibiotics in the treatment of pulpo-periapical infections. Previous studies [2,10,[14][15][16][17] have evaluated dentists' knowledge of antibioticprescribing habits. However, although it is known that dentists' prescribing habits are sometimes influenced by patient pressure, until now, no study had analyzed patients' knowledge and beliefs about antibiotic treatment in endodontics.…”
Section: Discussionmentioning
confidence: 99%
“…The author also highlighted the overprescription of antibiotics in endodontic infections and the need for improved prescription habits and education. Domínguez-Domínguez, L. (2021) [17] revealed that 44% of dentists prescribed antibiotics for symptomatic irreversible pulpitis, with up to 27% not following current guidelines, indicating a need for improved antibiotic prescription habits among Spanish general dentists. Alonso-Ezpeleta, O.…”
Section: Spainmentioning
confidence: 99%
“…Other surveys have demonstrated opportunities for improvement in antibiotic prescribing decisions for endodontic patients, [11][12][13][14][15][16] patients undergoing dental implant placement, 17,18 emergency dental care, [19][20][21] and general dentistry. [22][23][24][25][26] Other conditions, such as use of systemic antibiotics prior to periodontic treatments, have shown considerable variability. Work is underway to standardize candidate outcome sets for dental antibiotic stewardship.…”
Section: <001mentioning
confidence: 99%